Prevention of the Trend of Rational Choices Among Millennials in Early Marriage in Yogyakarta - Sumarkan, Sumarkan; Syihabuddin, Atok; Dikuraisyin, Basar; bin Abd. Ghani, Amirul Haqeem (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
This research reveals a new trend in the phenomenon of early marriageamong the millennial generation. The motives for early marriage haveundergone a transformative change, no longer driven by tradition, parentalintervention, cultural norms, or religious figures, but rather influenced byknowledge and personal choice as a result of digital applications. The studyalso describes the preventive measures taken by judicial institutions toprevent early marriage. This research is qualitative in nature, with primarydata obtained through interviews and document studies, includinginterviews with a sample of millennials and two judges from the YogyakartaReligious Court.. Key findings of this study are, first, the transformation ofearly marriage trends in Yogyakarta City stems from changes in social andlegal norms shaped by digital figures, trends, and framing. Thetransformation in millennials' thinking when making decisions about earlymarriage is due to compliance with norms and the most rational choice. Theydecided to marry early because it provided economic security amid economichardship. Second, judicial prevention is carried out through the issuance ofStandard Operating Procedures (SOPs) in courts for the legislation of earlymarriage applications through the SIDIKA application, as it aims to protectpersonal, social, and economic interests, which are part of the public interest(maslahah mulghah) aligned with the dimensions of maqasid shariah.